PENINGKATAN PERILAKU MENCUCI TANGAN DENGAN TEKNIK MODELING PADA KELOMPOK ANAK USIA SEKOLAH - Sri Wahyuni; Sigit Mulyono; Wiwik Wiarsih (Universitas Muhammadiyah Jember, 2017)
Hand washing is a simple action that can prevent a variety of diseases especially diarrhea, but this action is still rarely carried out by school children. This study aimed to increase hand washing behavior by modeling techniques at primary school age children ( 6-12 years ). The research design was quasi experiment consisting of two groups; 38 subjects as intervention groups and 38 subjects as control groups. The sampling technique used stratified random sampling, followed by simple random sampling. The results showed hand washing practices was increased by modeling activity (p=0.000). Behaviour modification with modelling techniques can be applied as one effort to increase hand washing behavior of school children that could be integrated in the school nursing service. Keywords: School age children, behavior modification, hand washing